Trompe Lo̓eil : Creating Decorative Illusions with Paint - Gordon-Smith, Roberta; Edited by Wormleighton, Alison (Newton Abbot David & Charles Book, 2001)
Providing an explanation of trompe l'oeil techniques using step-by-step photography to ensure an understanding of how each technique is achieved, this book offers trompe l'oeil projects ranging from simple colour washing and fading to more advanced compositions with shelves, ornaments and windows.
Include Color Illustrations and Index
Keywords: Trompe l'oeil painting